PERAN BADAN KESATUAN BANGSA DAN POLITIK DALAM MENGEMBANKAN NILAI PERSATUAN INDONESIA PADA SILA KETIGA PANCASILA DI KOTA PEKANBARU - Mansur Anuar; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the phenomenom that appears in the sosial environment of the people of Pekanbaru City. Based on the strategic plan (Renstra), revision for 2017-2022 On the website of the Pekanbaru National Unity and Political Unit (Bakesbangpol) on Determining Strategic Issues in the field of ideology and national insight, there is still a lack of public understanding of the four pillars of the Unitary State of the Republic of Indonesia. Likewise, there are so many people in the city of Pekanbaru who have different religious backgrounds, ethnicities and races, so it is feared that disintegration will occur which can damage the unity and integrity of the people of Pekanbaru city. The formulation of the problem in this study is how the role of the national and political unitary body in developing the value of indonesia unity in the third principle of Pancasila in the city of Pekanbaru. The purpose of the study was to determine the role of Bakesbanpol in developing the value of Indonesian unity in the third principle of Pancasila in the city of Pekanbaru. This research method is descriptive qualitative, the data collection instruments used are observation, interviews and documentation. Respondents in this study amounted to 6 people, 2 people from the National and Political Unity Agency (Bakesbangpol), 2 resource persons/presenters at Bakesbangpol socialization education and training and 2 people/audience at the Bakesbangpol event. Sampling technique using purposive sampling. The result of this research is that Bakesbangpol Pekanbaru city in carrying out its duties regarding its role in developing the values of Indonesian unity in the city of Pekanbaru can be said to have been carried out well. the role of important performance regarding socialization activities in the form of seminars by providing material related to national insight and increasing the noble values of the nation, coaching in the form of providing understanding to the community both from the workforce, social organizations (Ormas), political parties, as well as students and other associations to always hold fast to the values of Pancasila in the life of society, nation and state, provide reinforcements about the ideology of Pancasila well as monitoring in the form of evaluating activities that have been carried out.Keywords: Role, Bakesbangpol, The Value of Indonesian Unity